DETERMINATION OF FAMILY SUPPORT FOR SELF-MANAGEMENT OF HYPERTENSION PATIENTS - Noor Eswanti; Muhamad Jauhar; Novi Tiara; Lasmini Lasmini ((IJP) Indonesia Jurnal Perawat, 2026)
Hypertension is a chronic disease that requires long-term management through optimal self-management behavior. However, many hypertensive clients are still unable to consistently perform self-management behavior. One factor suspected of playing a role in improving self-management behavior is family support. This study aims to determine the relationship between family support and self-management behavior in hypertensive clients. This study used a quantitative design with a cross-sectional approach. The study sample consisted of hypertensive clients in the Dawe Community Health Center area, selected using a purposive sampling technique. The instruments used included a standardized family questionnaire containing family support sourced from (Nursalam, 2017) with a Cronbach Alpha value of 0.628 and the Hypertension Self-Management Behavior Questionnaire (HSMBQ) to measure self-management behavior. The data collection procedure was carried out by filling out the questionnaire directly. Data analysis was performed using the Spearman rho statistical test with a significance level of 0.05. The results of the study showed a significant relationship between family support and self-management behavior in hypertensive clients with a p-value of 0.000 and a correlation coefficient of 0.333, indicating a positive relationship with weak to moderate strength. It can be concluded that family support plays a role in improving self-management behavior in hypertensive clients. Therefore, nurses are expected to actively involve families in nursing care through family-based education and interventions to improve optimal hypertension management.